Alternatif Penyelesaian Sengketa Pada Sengketa Kepengurusan dan Penyelenggaraan Masjid Jami’ Nurul Huda dan Masjid An-Nur di Desa Bagan Percut Kecamatan Percut Sei Tuan - Muhardinata, Imam (Al-Fikru: Jurnal Ilmiah, 2019)
Every worship must fulfill the rules and procedures set by the Shari'ah, including the Friday prayer. One of the issues that is often discussed is the establishment of more than one Friday prayer in one village, or better known as ta'addud al-friday (which is Friday). The motives of the two Friday prayers in one village vary, sometimes due to the limited capacity of the mosque, due to conflicts between villagers, or limited to continuing the prevailing tradition. In conclusion, it is permissible for residents whose homes are far from the mosque, at least as far as 1,666 km, to establish a second Friday in the area. If it does not meet the aforementioned standards, then it is not permissible to establish a second Friday unless there are other reasons besides reasons of distance, such as limited capacity of the mosque or internal conflict that requires them to establish Friday in another place. Finally, the results of the mediation by the two parties to the dispute were agreed upon, contained in a statement signed by the residents of the hamlet XV, XVI, and XVII of the Percut village to the Indonesian Ulema Council, Percut Sei Tuan Sub-District, whose contents are as follows: 1. That both parties are willing to reconcile again about the establishment and reunification of the old and new BKM into a jami mosque 'and a new BKM named BKM jami mosque' Nurul Huda where the old mosque also continues to function as a place/educational institution or a foundation for the benefit of many members of the community, so that the value of waqf continues to function as it functions. 2. That whatever is the fatwa/decision of the Indonesian Ulema Council (MUI) in this case is submitted by the MUI of Percut Sei sub-district regarding the issue of a mosque dispute which will be declared valid as a jami 'mosque/highway that has the right to establish a Friday that has been deliberated on January 29, 2008 that the community agreed and obeyed and would carry out the best possible.